Literatue Review : Biochemical and Pharmacological Prospects of Enhalus acoroides as a Source of Antifibrotic Compounds for National Drug Development - Vivi Shofia (Jurnal Farmasi Udayana, 2025)
Fibrosis is a progressive pathological process characterized by excessive accumulation of extracellular matrix and represents a major cause of organ failure, including in the kidney, liver, and lung. Currently available antifibrotic therapies have limited efficacy and are associated with potential adverse effects, highlighting the urgent need for new drug candidates derived from natural sources. The seagrass Enhalus acoroides, which is abundant in Indonesian waters, has been reported to contain flavonoids, polyphenols, sterols, and bioactive fatty acids that may modulate oxidative stress and inflammation, two key mechanisms involved in fibrogenesis. This review aims to evaluate the biochemical and pharmacological potential of E. acoroides as a source of antifibrotic compounds for national drug development. The methodology involved a literature review of scientific databases focusing on phytochemical profiles, pharmacological activities, and molecular mechanisms related to fibrosis. The findings indicate that E. acoroides exhibits significant antioxidant and antibacterial activities, contains major secondary metabolites (notably flavonoids and phenolics), and shows mechanistic relevance to the TGF-β/Smad signaling pathway, a central regulator of fibrogenesis. In conclusion, E. acoroides has promising potential as a candidate antifibrotic phytopharmaceutical; however, further validation through in vitro, in vivo, and advanced pharmaceutical formulation studies is required